How complex is the hidden species diversity of the teleost Plotosus genus? - Elsa Froufe; André Gomes-dos-Santos; Ana Matos; Jonathan Wilson; Salman Malakpourkolbadinezhad; Daniel D. Pereira; Randal Singer; L. Filipe C. Castro (Ichthyological Research, 2024)
The striped eel catfish, Plotosus lineatus was first described by Thunberg in 1787 from the Indo-Pacific region in the East Indian Ocean. Since then, the species has been recorded in various marine and brackish habitats in Japan, southern Korea, the Ogasawara Islands, Australia, Lord Howe Island, Palau and Yap in Micronesia, East Africa to Samoa, Madagascar, Red Sea and the Persian Gulf. Occurrences of this species have also been registered in the Mediterranean Sea, a non-native location, indicating a possible biological invasion event. Despite its long history, the taxonomic status of the P. lineatus species complex remains puzzling and uncertain. Here, we analysed all the available mitochondrial cytochrome c oxidase subunit 1 sequences (NCBI and BOLD) from specimens covering the current known distribution range, in an attempt to clarify the evolutionary relationships of different lineages within this species. We deduce nine monophyletic Lineages - I–IX , of P. lineatus with Kimura-2P distances ranging from 2% to 16%, with a mean intraspecific distance of 6%. Strikingly, Lineage V is composed uniquely of Mediterranean-captured individuals, with an unknown evolutionary origin. These findings strongly suggest the need for a careful species taxonomic reassessment. Some Lineages are composed of individuals from specific geographic locations (e.g., Australia and Indonesia), while others include specimens from broader geographic areas (e.g., almost all Indo-Pacific coastline). Additionally, several deposited sequences are most likely the result of morphology-based misidentifications. Due to the biological invasive potential, as well as the use of the species as a valuable physiology model, the P. lineatus species complex requires further attention. Overall our study offers a clear framework for future comparative studies of striped eel catfish individuals captured from different ecosystems.

DiceCT for fishes: recommendations for pairing iodine contrast agents with μCT to visualize soft tissues in fishes - Matthew A. Kolmann; Ramon S. Nagesan; James V. Andrews; Samuel R. Borstein; Rodrigo Tinoco Figueroa; Randal A. Singer; Matt Friedman; Hernán López‐Fernández (Journal of Fish Biology, 2023)
Computed tomography (CT) scanning and other high‐throughput three‐dimensional (3D) visualization tools are transforming the ways we study morphology, ecology and evolutionary biology research beyond generating vast digital repositories of anatomical data. Contrast‐enhanced chemical staining methods, which render soft tissues radio‐opaque when coupled with CT scanning, encompass several approaches that are growing in popularity and versatility. Of these, the various diceCT techniques that use an iodine‐based solution like Lugol's have provided access to an array of morphological data sets spanning extant vertebrate lineages. This contribution outlines straightforward means for applying diceCT techniques to preserved museum specimens of cartilaginous and bony fishes, collectively representing half of vertebrate species diversity. This study contrasts the benefits of using either aqueous or ethylic Lugol's solutions and reports few differences between these methods with respect to the time required to achieve optimal tissue contrast. It also explores differences in minimum stain duration required for different body sizes and shapes and provides recommendations for staining specimens individually or in small batches. As reported by earlier studies, the authors note a decrease in pH during staining with either aqueous or ethylic Lugol's. Nonetheless, they could not replicate the drastic declines in pH reported elsewhere. They provide recommendations for researchers and collections staff on how to incorporate diceCT into existing curatorial practices, while offsetting risk to specimens. Finally, they outline how diceCT with Lugol's can aid ichthyologists of all kinds in visualizing anatomical structures of interest: from brains and gizzards to gas bladders and pharyngeal jaw muscles.

Awareness and use of biodiversity collections by fish biologists - Randal A. Singer; Shari Ellis; Lawrence M. Page (Journal of Fish Biology, 2020)
A survey of 280 fish biologists from a diverse pool of disciplines was conducted in order to assess the use made of biodiversity collections and how collections can better collect, curate and share the data they have. From the responses, data for how fish biologists use collections, what data they find the most useful, what factors influence the decisions to use collections, how they access the data and explore why some fish biologists make the decision to not use biodiversity collections is collated and reported. The results of which could be used to formulate sustainability plans for collections administrators and staff who curate fish biodiversity collections, while also highlighting the diversity of data and uses to researchers.